2014
DOI: 10.1016/j.bbamem.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Ion channel stability of Gramicidin A in lipid bilayers: Effect of hydrophobic mismatch

Abstract: Hydrophobic mismatch which is defined as the difference between the lipid hydrophobic thickness and the peptide hydrophobic length is known to be responsible in altering the lipid/protein dynamics. Gramicidin A (gA), a 15 residue β helical peptide which is well recognized to form ion conducting channels in lipid bilayer, may change its structure and function in a hydrophobic mismatched condition. We have performed molecular dynamics simulations of gA dimer in phospholipid bilayers to investigate whether or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 76 publications
2
17
0
Order By: Relevance
“…[48][49][50] The lipid-protein interactions, e.g., between the lipid head-groups and protein side-chains, have been shown to be very important in the gating mechanism. However, the interaction dynamics are very hard to characterize and not much data are available.…”
Section: Temporal Symmetry and Hysteresismentioning
confidence: 99%
“…[48][49][50] The lipid-protein interactions, e.g., between the lipid head-groups and protein side-chains, have been shown to be very important in the gating mechanism. However, the interaction dynamics are very hard to characterize and not much data are available.…”
Section: Temporal Symmetry and Hysteresismentioning
confidence: 99%
“…The effect of hydrophobic mismatch has been elucidated and shown to affect peptide orientation and function. 93 It has been shown that, although the channel conformation of gramicidin A is the most stable structure, it is possible for gramicidin A to change from channel to nonchannel conformation, depending on the local environment of the host bilayers. In more complex ion channels, such as in Kir2.2, an inwardly rectifying potassium channel, phosphatidylinositol 4,5-bisphosphate binding sites have been predicted from multi-scale simulations that show good agreement with experimental results.…”
Section: Atomistic Simulations Elucidating Lipid-protein Interactionsmentioning
confidence: 99%
“…For example, from the beginning of the ESR-technique development, biophysicists have accepted the spin labeling technique for the simplest ion channels, such as spin-labeled derivatives of gramicidin peptides [162] and spin-labeled gramicidin itself [163], labeled valinomycin and its analogs [164] (along with the NMR observations of the nuclear Overhauser effect of transfer of the nuclear spin polarization from one nuclear spin population to another one via cross-relaxation [165,166]; the same method has been applied to the gramicidin [167][168][169]), cecropin [170][171][172][173], zervamicin [174,175] (early labeled by deuterium [176], 13 C and 15 N for NMR measurements [177]), alamethicin [178][179][180][181][182], etc. It is noteworthy that gramicidin as well as valinomycin [183] are well known as the simple ion channels [184][185][186][187][188], which can be studied by spin labeling and magnetic resonance methods [189,190] (as well as ion-channel-forming valinomycin [191][192][193]); zervamicin is also well known as the ion-channel-forming agent, ion channel peptide and a good model for the membrane ion channels [194][195][196] with a well-studied gating mechanisms [197][198][199] which can operate not only in the native membranes, but also in the artificial micelles and lipid bilayers…”
Section: Towards the Mass-independent Isotopic Patch-clampmentioning
confidence: 99%